1990
DOI: 10.3354/meps066035
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and population structure of the necrophagous amphipod Eurythenes gryllus in the West European Basin

Abstract: During 3 cruises to the West European Basin benthopelagic nekton was captured by use of an acoustically released vertical array of 8 to 10 baited traps. The traps were exposed from 5 to 1000 m above the bottom. Nearly all of the 1692 amphipods trapped in total during 18 deployments were identified as the lysianassid amphipod Eurythenes gryllus Lichtenstein. Most individuals were recovered from traps deployed 15 m above the sea floor. Above 30 m, catch rates decreased significantly. However, the vertical distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 10 publications
3
41
1
Order By: Relevance
“…An equal sex ratio confirms the expectations of a continuously breeding population. This sex ratio coincides with that found in the North Atlantic Ocean (Charmasson & Calmet 1987, Christiansen et al 1990, but is markedly different from that found in the north-eastern Pacific (Baldwin & Smith 1987), in the central North Pacific (Ingram & Hessler 1987) and in the south-eastern Pacific at a depth of 7800 m (Thurston et al 2002), where females dominate. In our collections only Stn V showed preponderance of females.…”
Section: Sex Ratiosupporting
confidence: 80%
See 2 more Smart Citations
“…An equal sex ratio confirms the expectations of a continuously breeding population. This sex ratio coincides with that found in the North Atlantic Ocean (Charmasson & Calmet 1987, Christiansen et al 1990, but is markedly different from that found in the north-eastern Pacific (Baldwin & Smith 1987), in the central North Pacific (Ingram & Hessler 1987) and in the south-eastern Pacific at a depth of 7800 m (Thurston et al 2002), where females dominate. In our collections only Stn V showed preponderance of females.…”
Section: Sex Ratiosupporting
confidence: 80%
“…The ontogenetic migration postulated for Eurythenes gryllus (Christiansen et al 1990) may be complex. With increasing size, immature E. gryllus move up into the water column, adopting an abysso-pelagic rather than a benthic lifestyle (Ingram & Hessler 1983, Smith & Baldwin 1984, Charmasson & Calmet 1987, Christiansen et al 1990).…”
Section: Vertical Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…3) as evidence that juveniles rely on detrivory to a greater degree than adults. Similar ontogenetic shifts from mainly detrivory to carnivory have been noted in other lysianassoid species based on gut content analyses (Christiansen and Diel-Christiansen 1993), including Hirondellea gigas from the Philippine Trench (Hessler et al 1978). Adults have the capacity to withstand long periods between meals because of their lipids stockpiled from previous nutritious meals, but recently hatched individuals may not have this metabolic advantage (Ingram and Hessler 1987).…”
Section: Discussionmentioning
confidence: 56%
“…First, the deep sea is notoriously difficult to observe. Second, the majority of deep-sea scavenging amphipods are collected with baited traps (e.g., Shulenberger and Hessler 1974;Christiansen et al 1990;De Broyer et al 2004); amphipods with access to bait in traps almost always satiate themselves with it. Collection methods designed to prohibit deep-sea amphipods from consuming bait do exist, but they often collect amphipods with empty guts or guts containing amorphous material (Smith and Baldwin 1984;Sainte-Marie 1992).…”
mentioning
confidence: 99%